The effect of blended learning on tacking technique improvement in preteen sailing - Mohamed Abdelkader Souissi; Linda Toumi; Omar Trabelsi; Ismail Dergaa; Ahmed Ghorbel; Adnene Gharbi; Katja Weiss; Thomas Rosemann; Nizar Souissi; Beat Knechtle (Scientific Reports)
Abstract This study investigates the effects of two blended learning strategies on improving tacking technique in Optimist sailing among children aged 11–13. Specifically, it compares video feedback with online written instructions (BLIV) and online written instructions only (BLI). Thirty-one children aged 11–13 years old were randomly divided into three groups with different learning strategies: BLIV, BLI, and a control group (CONT). Each participant completed a pre-test (T0) and a post-test (T1) following a four-session learning unit. Evaluations focused on (i) tacking technique, rated by three sailing coaches, (ii) execution time measured using Kinovea software, and (iii) theoretical knowledge, assessed through a test involving error detection in a novice’s video. Statistical analyses revealed that the BLIV group demonstrated significant improvements at T1 in technical performance (p < 0.001, Hedges’ g = 2.71), execution time (p = 0.006, Hedges’ g = 1.14), and theoretical knowledge (p < 0.001, Hedges’ g = 1.98), outperforming the BLI and CONT groups in tacking performance. These findings underscore the effectiveness of the BLIV strategy in enhancing learning outcomes in environments with high levels of sensory distractions. By facilitating a deeper understanding of technique and error correction, this technology-enhanced instructional approach shows promise as a valuable tool for teaching complex motor skills in sports. The research findings suggest that BLIV demonstrates significant improvements in sailing skills, execution time, and theoretical understanding among young sailors compared to other methods. The study advocates for the integration of blended learning approaches that combine in-class activities with delayed video-based feedback delivered online to enhance skill acquisition young sailors.